Konsep Pemikiran Ekonomi Islam Imam Al-Ghazali - Zahra, Shofia; Janwari, Yadi (Eco-Iqtishodi : Jurnal Ilmiah Ekonomi dan Keuangan Syariah, 2023)
This research aims to the concept of Imam Al-Ghazali’s thought through his famous work, it is Ihya ‘Ulum Al-din, al-Mustashfa, Mizan Al-‘Amal and al-Tibr al-Masbuk fi Nasihat al-Muluk. The method used in this research is literature study. Based on the results, it can be seen that Imam Al-Ghazali’s concept of economic thinking is Maslahah oriented. Benefit in Al-Ghazali’s perspective consists of dharuriyah, hajiyah and tahsiniyah. Business orientation in the economic cycle doesn’t only prioritize worldly life but is also oriented toward the afterlife. Apart from that, the ideas related to the economy consist of exchance and market evolution, production activities and hierarchies, the barter system and the function of money, the role of the state in fair, peaceful, and stable economic development, and public finance.